Genetic variation and tolerance indices interactions among wheat (Triticum aestivum L.) accessions under drought stress - Olumekun, Victor Olugbenga; Ajayi, Abiola Toyin; Ibidapo, Oluwasegun Victor (Journal of Pure and Applied Agriculture, 2023)
This study was conducted to analyse the level of genetic variability for drought tolerance among wheat (Triticum aestivum L.) accessions adopting the technique of stress tolerance indices of quantitative traits. A factorial experiment (10 x 2) in a completely randomised design replicated three times was adopted utilising pots (300 pots in total) filled with 3.5 kg of unfertilised top soil. Two treatments were applied (after irrigating all pots with 500 ml for two weeks after seed sowing): control (irrigated with 500 ml of water per pot at 2 days interval) and drought stress (irrigated with 500 ml of water at 8 days interval). Targeted data were on plant height and number of tillers per pot, number of spikelets per spike, spike length, seeds per spike, 1000 grain weight and grain yield